Kazimierz Bartoszyński w Poznaniu - Wysłouch, Seweryna (Przestrzenie Teorii, 2015)
The author of this article discusses Kazimierz Bartoszyński’s didactic activity and writings, i.e. his doctoral thesis titled O powieściach Fryderyka Skarbka [On Fryderyk Skarbek’s Novels] (which was published in 1963) and his later articles on the gawęda (i.e. a story stylized as an oral tale) and historical novel (which are collected in the volume titled O polskich prozach powieściowych – słynnych i nieco zapomnianych [On Polish Prose Novels – Those Famous and Slightly Forgotten Ones] (2011)). These writings were a continuation of the studies of the 19th-century novel that had been conducted in Poznań.